Reformasi Haul Zakat di Masa Pandemi dalam Tinjauan Empat Mazhab - Andi Muh. Taqiyuddin; A.Qadir Gassing; Muammar Muhammad Bakry (International Journal of Education and Literature, 2023)
This study aims to determine the concept of haul in the perspective of four schools of thought. This research is a type of qualitative research with library research methods. This study uses a normative language and juridical approach. The data are sourced from various literature explorers whose sources are journals, books and proceedings. Data analysis is used by tracing various literatures from articles, books, proceedings and other relevant, analyzing and drawing conclusions. The results of the study are that First, according to the agreement of the scholars, among them according to the four schools of thought that haul is not required for agricultural and fruit zakat. Second, the concept of expediting the payment of zakat before the haul during the pandemic, there is no difference among the four schools of thought, in fact what is wrong is the paradigm of society, the way of thinking, the way of understanding their knowledge is wrong, therefore there must be an effort to reshuffle the paradigm through reformulation of the zakat haul in the future. pandemic, namely the adjustment of the zakat haul during the pandemic.